All that wheezes is not asthma: A cautionary case study of shortness of breath in pregnancy. (September 2015) - Varnier, Nicla A; Chwah, Sarah; Miller, Trent; Pettit, Franziska; Brown, Mark; Rees, David; Henry, Amanda
Background: Shortness of breath is a common physiological pregnancy presentation, secondary to both hormonal and mechanical effects. Its pathological causes are common (asthma exacerbation or infection); new-onset cardiac pathology is rarely considered. Case: JC, a 39-year old G4P2T1, presented at 34 weeks' gestation with shortness of breath unrelieved by salbutamol. History included asthma, poly-drug abuse and smoking. Initial presentation was consistent with asthma exacerbation and she was treated as such. There was deterioration of symptoms and on re-examination raised jugular venous pressure was noted with bibasal lung crepitations and cardiac systolic murmur. Echocardiogram showed severe cardiomyopathy (left ventricular ejection fraction 20%). JC was commenced on diuretics, digoxin and fluid restricted. Labour was induced at 35 weeks' gestation, with birth of a healthy female infant (BW 2475 g) by elective assisted vaginal delivery. Cardiac function improved in subsequent weeks, confirming peripartum cardiomyopathy. Conclusion: Peripartum cardiomyopathy affects 1 in 2500–4000 live births. Over 90% of women regain normal cardiac function postpartum with optimal medical management. Peripartum cardiomyopathy presents a diagnostic conundrum as its primary symptoms mimic not only those of normal pregnancy but also a number of other, more common conditions. It is important to consider cardiac causes of shortness of breath initially, and vital to revisit an initial non-cardiac shortness of breath diagnosis if there is no sustained improvement with treatment. In this case, asthma history and initial wheeze on examination impeded correct diagnosis; however, the situation was re-evaluated and correct diagnosis made when the patient's shortness of breath deteriorated. Subsequent multidisciplinary management and birth in an appropriate setting facilitated the best outcome for both mother and baby.